Nanotubes and Nanowires - Burke, Peter John (World Scientific, 2007)
The field of nanotubes and nanowires is evolving at a rapid pace, with many potential applications in electronics, optics, and sensors, to name a few. In this book, various prominent researchers summarize our current understanding of these new materials systems, as well as some of these potential applications. A snapshot of the state-of-the-art in the field of nanowires and nanotubes, the contributions give an instructive mix of experimental, theoretical, and visionary material to give the reader an indication of where the field is now, and where it is going. With several points of view repres.
Keywords: Nanotubes.; Nanowires.; Nanostructured materials.; elektronické knihy; electronic books